Bologna Process in Armenia and Belarus: Successes and Problems - L. G. Titarenko; M. I. Zaslavskaya (Высшее образование в России, 2020)
The purpose of the article is to give a comparative analysis of the problems and achievements of the implementation of Bologna principles in higher education systems of the republics of Armenia and Belarus. Based on data from 2017–2019, a comparative study of the modernization of higher education systems of the two countries based on expert survey methods (experts are the administration and the teaching staff of universities), focus groups, content analysis of national media, statistics, and student surveys (only in Belarus), the authors identify the achieved successes and reveal unresolved problems in the process of implementing Bologna principles. It is shown that both countries formally ensured an equal access to higher education for their citizens, employment opportunities for graduates, participation of students and teachers in mobility processes; in both countries, a two-stage system of education and a system of transfer points, as well as a new pedagogical paradigm and competency-based approach have been introduced. At the same time, both countries are experiencing significant objective difficulties, associated primarily with insufficient state funding for higher education systems, inconsistencies between different levels of government, bureaucratization and inertia in the practical implementation of new approaches. Therefore, even with the formal implementation of the Bologna principles in Armenia, the national higher education system did not become a full-fledged participant in the European Higher Education Area. As for Belarus, its priorities remain the national principles of education, which define the boundaries of any educational reforms, including Bologna.